Thermohydraulic analysis of Tore Supra/WEST TF coil quench: Associated smooth quench occurrence in tokamak. (March 2020) - Nicollet, S.; Torre, A.; Girard, S.; Lacroix, B.; Reux, C.; Prochet, P.; ,
Highlights: Thermo-hydraulic studies and analysis on the TS/WEST Toroidal Field Coil. CICC-like Winding Pack SuperMagnet Model with conductors and superfluid helium. Quench (runaway electrons) transient calculations and benchmark with measurements. Smooth quench criticality and possible occurrence at low field region. Importance of one secondary quench detection for magnets safe operation. Abstract: The Toroidal Field (TF) system of the Tore Supra/WEST tokamak comprises 18 NbTi superconducting coils, cooled by a static superfluid helium bath at 1.8 K and carrying a nominal current of 1255 A. The 19th December 2017, at the end of plasma run #52205, a quench of TFC-09 was detected first on a secondary thermohydraulical signal (helium liquid level) and triggered the current Fast Safety Discharge (FSD). A numerical model of this quench has been developed with SuperMagnet (CryoSoft). The whole TFC-09 circular coil is modelled by THEA as a single large Cable-In-Conduit Conductor (CICC) with 2028 large rectangular strands (monolithic conductors of length equal to coil average perimeter). The external quench helium relief circuit (cold and warm safety valves, rupture disk and magnetic valve with corresponding pressure set) is modelled by FLOWER. The helium pressure in the coil, upstream of the cold safety valve (maximum value of 9 bar), and the expulsed helium temperature have been used as comparison between measurements and calculations which depend on the Minimum Quench Energy (MQE) used in THEA with small initial heat deposition length (few tens of centimeters) at low field region (external leg). This energy, in the order of few kJ, is compared to the real shape and energy of neutron and gamma flux caused by highly energetic runaway electrons colliding the outboard plasma facing components and which induced the quench. The expulsed helium mass flow rate of nearly 6 kg/s during 5 s has also been calculated. This event confirms on one hand the criticality and the possible occurrence of a so called "smooth quench" caused by small initial heat deposition length and at low field region and on the other hand the important interest of secondary quench detection which can be useful for other tokamak magnets safe operation and protection.